Experimental study of the effects of sub- and super-critical CO2 saturation on the mechanical characteristics of organic-rich shales. (1st August 2017) - Yin, Hong; Zhou, Junping; Xian, Xuefu; Jiang, Yongdong; Lu, Zhaohui; Tan, Jingqiang; Liu, Guojun
Abstract: The interaction between carbon dioxide (CO2 ) and shale during the process of CO2 sequestration and shale gas recovery could significantly affect mechanical properties of the shale. In the current study, we performed experiments at 38 °C on shale samples from the Sichuan Basin aiming at investigating the effects of sub-critical CO2 (SubCO2 ) and super-critical CO2 (ScCO2 ) saturation on shale mechanics. Uniaxial compressive strength (UCS) test, X-ray diffraction (XRD) analysis, energy dispersive X-ray spectroscopy (EDX) analysis and acoustic emission (AE) analysis were conducted on the raw and CO2 -saturated (4, 6, 8, 12 and 16 MPa) shale samples. Results indicate that SubCO2 saturation (4 and 6 MPa) causes reduction in UCS and elastic modulus (E) of the shale up to 22.9% and 23.1%, respectively. More significantly, ScCO2 saturation (8, 12 and 16 MPa) causes up to 33.9% reductions of UCS and 34.0% reduction of E. This phenomenon can be attributed to a higher adsorptive potential and dissolution capacity of the ScCO2 fluid. In addition, these two parameters gradually vary with increasing saturation pressure: They slowly decrease and reach minimum values at 12 MPa, and then slightly increase as the saturation pressure increases from 12 to 16 MPa because of the compression effect resulted from higher fluid pressure. Results of AE analysis show that, compared with the raw shale samples, cracks of the CO2 -saturated samples have a longer closure stage while a shorter stable and unstable crack propagation stage. It reveals that mechanical weakening of the shale is controlled by microscopic damages that resulted from CO2 saturation. Overall, our study confirms that the influence of CO2 saturation on the mechanical characteristics of organic-rich shale samples is closely related to gas pressure and phase state of CO2 . Highlights: Influence of sub- and super-critical CO2 saturation on the UCS and E of organic-rich shales was studied. Reduction in UCS of organic-rich shales caused by SubCO2 and ScCO2 saturation is 22.86% and 33.89% respectively. Reduction in E of organic-rich shales caused by SubCO2 and ScCO2 saturation is 23.10% and 33.97% respectively. Effects of CO2 saturation on mechanical properties of shales is highly depending on pressure and phase state of CO2 .